2018
DOI: 10.21475/ajcs.18.12.02.pne716
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical activity in Brazilian Cerrado soils is differentially affected by perennial and annual crops

Abstract: Organic matter mineralization depends on how microbiota access nutrients, substrates and soil fertilization. This study shows influence of perennial (sugarcane) and annual (soybean and corn) crops on the activity of enzymes participating in the carbon, nitrogen and phosphorus cycles and proposes using hydrolases as bioindicators of soil quality. Samples were collected, during dry season and rainfall, in six different plots where sugarcane, soybean, corn and native Cerrado soils could be found at the same locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…When the native Cerrado vegetation is converted to shallow‐rooted, nonpermanent croplands, changes in the interaction between water and soil occur (Cabral, da Rocha, Gash, Freitas, & Ligo, ). Land conversion modified soil pH, bulk density and available P and K for croplands (Zago et al, ), while pollution of some rivers and streams by pesticides exceeds the Brazilian and European Union (EU) water quality limits (Hunke, Mueller, Schröder, & Zeilhofer, ). In Brazil, the use of fertilizers doubled from 80 to 160 kg/ha between 1992 and 2012 (IBGE, ) and the application of pesticides added 3.5 kg of petrochemicals per hectare, making Brazil the largest agricultural user of chemical fertilizers and pesticides per capita and per area (Wittmann et al, ).…”
Section: The Link Between Terrestrial and Freshwater Habitatsmentioning
confidence: 99%
“…When the native Cerrado vegetation is converted to shallow‐rooted, nonpermanent croplands, changes in the interaction between water and soil occur (Cabral, da Rocha, Gash, Freitas, & Ligo, ). Land conversion modified soil pH, bulk density and available P and K for croplands (Zago et al, ), while pollution of some rivers and streams by pesticides exceeds the Brazilian and European Union (EU) water quality limits (Hunke, Mueller, Schröder, & Zeilhofer, ). In Brazil, the use of fertilizers doubled from 80 to 160 kg/ha between 1992 and 2012 (IBGE, ) and the application of pesticides added 3.5 kg of petrochemicals per hectare, making Brazil the largest agricultural user of chemical fertilizers and pesticides per capita and per area (Wittmann et al, ).…”
Section: The Link Between Terrestrial and Freshwater Habitatsmentioning
confidence: 99%
“…Nunes et al (2011) evaluated management systems and organic matter contents in Oxisol of the Cerrado biome with a soybean-corn succession, and found that the least cultivated systems had lower MO levels than the pasture production systems. Santana et al (2016) and Zago et al (2018) highlight that land use and management system exert a profound influence on nutrient supply, since it directly affects the soil microbiota, influencing the decomposition of MO and mineralization of nutrients to the soil. However, the systems studied differed from the natural Cerrado on several of the chemical properties studied, corroborating the findings of Carneiro et al (2009).…”
Section: Discussionmentioning
confidence: 99%
“…Soil properties in the native Cerrado area are defined by the vegetation and deposition of organic matter, while soil exploration by the roots increases its structural quality, nutrient availability and creates a microclimate in the region (Silva Júnior et al, 2012;Abreu et al, 2016;Zago et al, 2018). Roots also protect the soil against direct exposure to sunlight and the impact of rainwater, which can disaggregate the soil and carry its nutrients by runoff.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transformations coming from anthropic action alter composition and amount of organic matter of the soil and directly affect its physical and chemical properties. These transformations imply perturbations and directly influence the microorganisms, microbial processes and nutrient cycling in the soil (Zago et al, 2018).…”
Section: Introductionmentioning
confidence: 99%